Auto Tank Gauge System Analysis for Monitoring Stock Liquefied Petroleum Gas di integrated Palembang Terminal - Muhammad Febrian Islami; Nita Nurdiana; Yudi Irwansi (Green Engineering: International Journal of Engineering and Applied Science, 2025)
Measuring Liquefied Petroleum Gas (LPG) levels and inventory in storage tanks is a critical aspect of terminal operations, directly influencing safety, operational efficiency, and accurate stock management. The Integrated Terminal Palembang – Pulau Layang LPG Site has implemented a servo-type Automatic Tank Gauging (ATG) system, namely the Proservo NMS81, to provide precise and real-time volume measurements. Despite its operational importance, there remains a limited in-depth understanding of how this ATG system functions, particularly regarding the complete process from sensing LPG levels to converting them into accurate inventory data. This study aims to analyze the working mechanism of the Proservo NMS81 in measuring LPG height and generating digital stock data for monitoring purposes. The research method combines a literature review of the Proservo NMS81 technical datasheet and related scientific references with direct field observation (KSM-LP) at the LPG Pulau Layang site. The analysis covers the operating principle of the servo sensor, which relies on displacement measurement via a mechanical float and wire system; the analog-to-digital conversion process utilizing a 12-bit ADC to transform continuous signals into discrete digital values; the communication protocols employed, including HART and Modbus RS-485, for transmitting processed data to the control system; and the algorithmic data processing that converts tank level measurements into standardized inventory figures based on tank calibration tables and product density. The results of this study are expected to improve technical knowledge regarding servo-type ATG systems, enhance the accuracy and reliability of inventory monitoring, and contribute to more informed operational decision-making. Furthermore, the research findings are intended to serve as a valuable academic reference for the application of advanced instrumentation technology in the energy industry, supporting both professional practice and further scholarly exploration in the field.